Randomized pharmacokinetic study comparing subcutaneous and intravenous palonosetron in cancer patients treated with platinum based chemotherapy. - Belen Sadaba; Anabel del Barrio; Miguel Angel Campanero; Jose Ramon Azanza; Almudena Gomez-Guiu; Jose Maria Lopez-Picazo; Salvador Martin Algarra; Francisco Guillén Grimá; Maria Blanco Prieto; Jose Luis Perez-Gracia; Alfonso Gurpide (PLoS ONE)
Background Palonosetron is a potent second generation 5- hydroxytryptamine-3 selective antagonist which can be administered by either intravenous (IV) or oral routes, but subcutaneous (SC) administration of palonosetron has never been studied, even though it could have useful clinical applications. In this study, we evaluate the bioavailability of SC palonosetron. Patients and methods Patients treated with platinum-based chemotherapy were randomized to receive SC or IV palonosetron, followed by the alternative route in a crossover manner, during the first two cycles of chemotherapy. Blood samples were collected at baseline and 10, 15, 30, 45, 60, 90 minutes and 2, 3, 4, 6, 8, 12 and 24 h after palonosetron administration. Urine was collected during 12 hours following palonosetron. We compared pharmacokinetic parameters including AUC0-24h, t1/2, and Cmax observed with each route of administration by analysis of variance (ANOVA). Results From October 2009 to July 2010, 25 evaluable patients were included. AUC0-24h for IV and SC palonosetron were respectively 14.1 and 12.7 ng × h/ml (p=0.160). Bioavalability of SC palonosetron was 118% (95% IC: 69-168). Cmax was lower with SC than with IV route and was reached 15 minutes following SC administration. Conclusions Palonosetron bioavailability was similar when administered by either SC or IV route. This new route of administration might be specially useful for outpatient management of emesis and for administration of oral chemotherapy. Trial registration ClinicalTrials.gov NCT01046240.